Hubungan Antara Status Gizi dengan Siklus Menstruasi pada Mahasiswi Pendidikan Dokter Universitas Lampung Angkatan 2021 - Hasanah, Sabila; Zuraida, Reni; Suharmanto, Suharmanto; Mutiara, Hanna (Medula, 2024)
A normal menstrual cycle reflects good reproductive health and plays an important role in preparing the body for pregnancy. Based on the 2018 Basic Health Research, around 13.7% of women aged 10-59 years experienced irregular menstruation. One of the factors that can interfere with the normalcy of the menstrual cycle is abnormal nutritional status. This study aims to determine whether there is a relationship between nutritional status and the menstrual cycle in University of Lampung Medical Education students class of 2021. The type of research used was analytical observational with a cross-sectional approach, which was carried out from November 2024 to January 2025, involving 123 female students selected through simple random sampling technique. Data on nutritional status was obtained from the calculation of Body Mass Index (BMI), while menstrual cycle data was obtained using a menstrual cycle sheet. The results of the analysis using the mann-whitney test showed a p-value of 0.083 (p-value>0.05), which indicated that there was no significant relationship between nutritional status and menstrual cycle among University of Lampung medical education students Class of 2021.